2022
DOI: 10.1101/2022.06.12.495838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melanopsin activates divergent phototransduction pathways in ipRGC subtypes

Abstract: Melanopsin signaling within ipRGC subtypes impacts a broad range of behaviors from circadian photoentrainment to conscious visual perception. Yet, how melanopsin phototransduction within M1-M6 ipRGC subtypes impacts cellular signaling to drive diverse behaviors is still largely unresolved. The identity of the phototransduction channels in each subtype is key to understanding this central question but has remained controversial. In this study, we resolve two opposing models of M4 phototransduction, demonstratin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Our overall phototransduction work on ipRGCs ( 16 18 ), including the current data, share only limited agreement with that from another group ( 23 25 ). This other group agreed on the existence of the PLCβ4/TRPC pathway, but has not clearly acknowledged the existence of a cyclic-nucleotide-mediated phototransduction pathway ( 23 , 25 ).…”
supporting
confidence: 56%
“…Our overall phototransduction work on ipRGCs ( 16 18 ), including the current data, share only limited agreement with that from another group ( 23 25 ). This other group agreed on the existence of the PLCβ4/TRPC pathway, but has not clearly acknowledged the existence of a cyclic-nucleotide-mediated phototransduction pathway ( 23 , 25 ).…”
supporting
confidence: 56%
“…The melanopsin photocurrent is different from rod/cone evoked synaptic currents in that its duration is very prolonged, even when presented with a very short light pulse (Fig. S1) (Contreras et al 2023). We observed that sOn-α cells in Fmr1(-/y) retinas had slightly larger, more prolonged blue light evoked currents (Fig.…”
Section: Figure S3 Resultsmentioning
confidence: 67%
“…We identified sOn-α cells based on physiological and molecular features that are unique to this cell type (see Methods and Fig. S2) (Contreras et al 2023) and filled these cells with neurobiotin to visualize their dendrites (Fig. 1B-C).…”
Section: Son-α Cells Have Denser Dendrites In Fmr1(-/y) Micementioning
confidence: 99%
“…The identities of M1, M2, and M3 ipRGCs were established using both dendritic stratification, soma size, and light responses. Cells with only OFF ramified dendrites were classified as M1 ipRGCs, cells with only ON stratified dendrites were identified as M2 ipRGCs, and bistratified cells were classified as M3 ipRGCs (M1: OFF; M2: ON; M3 ON/OFF) (Schmidt et al, 2008;Schmidt and Kofuji, 2009;Lee and Schmidt, 2018;Contreras et al, 2023). All cells identified as M2 were confirmed negative for SMI-32 immunolabeling, to ensure any cells with large somata were not M4 ipRGCs (data not shown) (Lee and Schmidt, 2018;Contreras et al, 2023).…”
Section: Electrophysiology and Analysismentioning
confidence: 99%
“…For experiments measuring the intrinsic melanopsin response to a 50ms light stimulus (6.08 × 10 15 photons • cm -2 • s -1 ), cells were voltage clamped at -60 mV. We measured the maximum amplitude of the light response for each cell, using a similar analysis described in Contreras et al, 2023. Cells were smoothed using a 100ms sliding average.…”
Section: Electrophysiology and Analysismentioning
confidence: 99%